The Nature and Significance of the Regional Educational Markets in the Conditions of the Transborder Cooperation (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The mean and significance of the educational market was learnt, the factors of the educational market of the border are as were determined, the directions of transborder cooperationin the sphere of education were analyzed, the levels of regulation of the regional educational markets in the conditions of the transborder cooperation were identified. Educational market in terms of transborder cooperation is a system of relationships of the border areas of neighboring countries for the purchase and sale of educational services. The result of transborder cooperation in the field of education is improving of the quality and competitiveness of educational services according to European requirements. The directions of development of the educational market in the conditions of transborder cooperation are enhancing institutional capacity of the public servants, strengthening the role of civil society, decentralization and regionalization of education, using the resources of international technical assistance and international experience, development of infrastructure of education, introduction of new technologies.The development of the education market is a priority of state and regional policy, which is able to increase the level of social and economic development of the region and has an important role in the European integration of Ukraine.
Keywords: educational service, educational market, transborder cooperation